Identification of key taste components in Baccaurea ramiflora Lour. fruit using non-targeted metabolomics - Jie Chen; Fengnian Wu; Huachen Wang; Chunce Guo; Wengen Zhang; Peisi Luo; Jing Zhou; Wenwen Hao; Guangyao Yang; Jianjian Huang (Food Science and Human Wellness)
Among the numerous fruit species of Baccaurea ramiflora Lour., ‘LR’ (white flesh) and ‘BR’ (pink flesh) are two kinds of local strains with high edibility. In order to study the metabolic causes of taste differences, we performed the non-targeted metabonomics analysis of ‘LR’ and ‘BR’ using LC-MS/MS. 541 metabolites were totally identified, and 45 kinds of metabolites (carbohydrates, fatty acids, flavonoids and terpenoids, etc.) were different between the two strains. The results indicate L-sorbose, D-(+)-glucose, citric acid, L-phenylalanine and oleamide, α-eleostearic acid were the main primary metabolites. The significant difference existed in pathways of unsaturated fatty acids between the studied two strains by pathway enrichment analysis. The results demonstrate that the different in composition, as well as the abundance of primary and secondary metabolites may be the potential causes of taste differences, which provides a new insight into the possible metabolic factors setting off the changing taste of B. ramiflora.